SOCIAL MEDIA INFLUENCER IMPLEMENTATION ON CONSUMER PURCHASE INTEREST - Eliyanti Agus Mokodompit; Hardi Fardiansyah; Leny Yuliyani (Jurnal Ekonomi, 2023)
Technology, such as social media apps, has made communication and relationship building easier. The use of influencers is one of the actors that contributes to the success of digital marketing platforms such as social media. Effective marketing entails keeping products in the forefront of consumers' minds so that they will choose to purchase the products offered. The goal of this research is to determine how digital marketing uses social media influencers to influence consumer purchasing behavior. According to the AISAS flow, micro-influencers, macro-influencers, and mega-influencers can create interesting content that sways the interests of a large number of consumers. The number of likes and comments on influencer accounts can indicate how interested followers are in the account. Influencers can also convey various types of promotions via their visual style and personal language. This is demonstrated by the use of interesting photography and copywriting. The potential for affected netizens to search for products (search), buy products (action), and leave product reviews is obvious, which can have an impact on companies that can promote their products to influencers. Important Instagram statistics and trends for 2022, for example, advertisers could reach 1.440 billion Instagram users in July 2022, ranking it as the world's fourth most 'active' social media platform. Instagram restricts its platform to people aged 13 and up, so knowing that 45.8 percent of the eligible audience in Indonesia is using Instagram in 2022 is useful. As a result, influencer marketing is quickly becoming one of the most popular marketing strategies for influencers, as they can present posts that promote brand image and characteristics, which have a significant impact on consumers.